PENANGANAN HAMBATAN SISWA DALAM MATERI PYTHAGORAS DENGAN QUANTUM TEACHING BERSTRUKTUR CONTEXTUAL MATHEMATICS DI SMP - Resty Rahayu Widiastuti; Sugiatno Sugiatno; Bistari Bistari (Universitas Tanjungpura, 2019)
AbstractThe students’ mastery of SMPN 05 Pontianak in Pythagorean material has many obstacles. This study aims to explain the process of handling obstacles with the approach of Quantum Teaching Structured Contextual Mathematics which in the process of handling will involve students in meaningful learning experiences. The research method is a Qualitative Descriptive research method with a Pedagogic approach. The subjects were 6 students who had the most obstacles in Pythagorean material. The data collection tool used was a test (pretest and posttest) and interview. Based on the results of the analysis of the research found obstacles students in Pythagorean material. The obstacle is understanding in applying and understanding the meaning of the Pythagorean concept. Then the handling is given according to the obstacles found, namely the Quantum Teaching Approach that has the characteristic